ISOLATION OF BIOACTIVE COMPOUNDS FROM DICRANACEAE MOSSES - Junairiah Junairiah; Tri Nurhariyati; Ni'matuzahroh Ni'matuzahroh; Lilis Sulistyorini (Universitas Airlangga, 2016)
ABSTRACT Dicranoloma reflexum and Dicranella coarctata are mosses from Dicranaceae family. This study was purposed to identify bioactive compounds contained from both species. Dicranoloma reflexum and Dicranella coarctata collected form Cangar forest, Batu, East Java. Mosses was rinsed, dried and crushed into powder. Extraction was performed using maceration method with n-hexane, acetic acid, and methanol solvent. Compounds obtained then identified using Gass Chromatography Mass Spectra. Result showed that n-hexane, acetic ethyl, and methanol extract of Dicranoloma reflexum contained 61, 16, and 58 compounds respectively. Main component of each extract was 1-octadecene, phenol, and 9-octadecanoic acid. N-hexane, acetic ethyl, and methanol extract of Dicranella coarctata contained 5, 38, and 23 compounds respectively. Main component of each extract was thiosulphuric acid, E-15 heptedecenal, and n-hexadecanoic acid.Key words : Dicranaceae, bioactive compounds